Using XSLT - Floyd, Michael (Que, 2002)
Special Edition Using XSLT starts with an overview explaining how XSLT fits into the bigger picture of the Extensible Stylesheet Language, and the differences between XSLT and XSL-FO. It then demonstrates practical examples of XSL transformations from XML to a variety of other useful formats including HTML, PDF, SVG and others. Later chapters discuss developer techniques for implementing XSLT within dynamic web environments including ASP and JSP. The author also covers debugging techniques and how XSLT relates to .NET. The book finishes with a useful reference section including detailed coverage of XSLT, XPath and XSL-FO.